The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/2358-2936e2019002
|View full text |Cite
|
Sign up to set email alerts
|

Population and reproductive biology of two caprellid species (Crustacea: Amphipoda) associated to Sargassum cymosum (Phaeophyta: Fucales) on the southeast coast of Brazil

Abstract: Caprellid amphipods are common crustaceans at Sargassum beds of southeastern Brazil and constitute an important link between primary producers and marine consumers. The goal of this study is to evaluate population and reproductive biology of two caprellid species: Paracaprella tenuis Mayer, 1903 and Pseudaeginella montoucheti Quitete, 1971. Sargassum cymosum Agardh, 1820 samples were collected monthly between October 2010 and September 2011 in a rock shore in southeastern Brazil. The caprellids were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 61 publications
2
3
1
3
Order By: Relevance
“…For E. pectenicrus , to the best of our knowledge, no previous information is available, but for a closely related species, Elasmopus levis , 22.3 ± 2.1 (standard error) embryos per female were reported, which is over a three-fold difference ( Borowsky, 1986 ). The fecundity values obtained are lower than those reported for cultured (36.3 eggs/embryos per female in C. scaura in average) ( Baeza-Rojano et al, 2013a ) and wild caprellids (from 2 to 55 in Pseudaeginella montoucheti and from 2 to 13 eggs in P. tenuis ) ( Garcia, Cunha & Jacobucci, 2019 ). Caprellids, unlike gammarids, show a relatively sedentary behavior (low energy expenditure) that could explain their higher fecundity; however, the active behavior of gammarids could be advantageous stimulating feeding responses, as previously observed when feeding S. officinalis hatchlings ( Baeza-Rojano et al, 2010 ).…”
Section: Discussioncontrasting
confidence: 64%
“…For E. pectenicrus , to the best of our knowledge, no previous information is available, but for a closely related species, Elasmopus levis , 22.3 ± 2.1 (standard error) embryos per female were reported, which is over a three-fold difference ( Borowsky, 1986 ). The fecundity values obtained are lower than those reported for cultured (36.3 eggs/embryos per female in C. scaura in average) ( Baeza-Rojano et al, 2013a ) and wild caprellids (from 2 to 55 in Pseudaeginella montoucheti and from 2 to 13 eggs in P. tenuis ) ( Garcia, Cunha & Jacobucci, 2019 ). Caprellids, unlike gammarids, show a relatively sedentary behavior (low energy expenditure) that could explain their higher fecundity; however, the active behavior of gammarids could be advantageous stimulating feeding responses, as previously observed when feeding S. officinalis hatchlings ( Baeza-Rojano et al, 2010 ).…”
Section: Discussioncontrasting
confidence: 64%
“…The sex ratio deviated for males as recorded in this study was already observed for other caprellid species, such as Paracaprella tenuis Mayer, 1903and Pseudaeginella montoucheti Quitete, 1971(Garcia et al 2019. The predominance of males suggests an intraspecific competition for females (Powell and Moore, 1991).…”
Section: Population Structure Of the Caprellids Associated With Sargassumsupporting
confidence: 81%
“…According to De Paula et al (2016), the reproductive biology evaluation of the caprellid amphipods of Lázaro Beach indicated a more intense reproduction in autumn and winter. Other caprellid species, such as Paracaprella tenuis and Pseudaeginella montoucheti, which were recorded in the same area as the present study, showed higher densities in winter (Garcia et al 2019). This indicates possible competitive interactions among those caprellids and Caprella species.…”
Section: Temporal Dynamics Of the Caprellids Associated With Sargassumsupporting
confidence: 78%
See 2 more Smart Citations